The role of pharmaceutical care in the use of rifaximin for the treatment of diarrhea - Temirova, Olena; Marchuk , Daria (The Ukrainian Scientific Medical Youth Journal, 2024)
the management of diarrhea represents a prevalent issue within the realm of healthcare. Rifaximin is recommended to treat traveler's diarrhea and irritable bowel syndrome. At the same time, it is important to rationally use an antimicrobial drug to prevent the development of antimicrobial resistance. Aim: to evaluate the role of pharmaceutical care in using rifaximin to treat diarrhea, based on a questionnaire. A questionnaire survey was done among 55 pharmacy professionals and 42 pharmacy visitors regarding the dispensing and use of rifaximin for diarrhea treatment. The survey of pharmacy visitors revealed that rifaximin was used for the treatment of small intestinal bacterial overgrowth syndrome (32 cases), traveler's diarrhea (7 cases), and irritable bowel syndrome with diarrhea (3 cases). Patients did not undergo stool culture before rifaximin prescription, which could have prevented antimicrobial resistance and ruled out other causes of diarrhea. It was found that 14% of respondents reported improvement the next day, while 83.3% reported improvement within three days. Pharmacists can educate visitors about the importance of completing the treatment course. Five percent of respondents reported nausea as an adverse reaction. Pharmacists dispensed rifaximin for the treatment of diarrhea in adults almost three times more often than in children. The tablet form of the drug was used in 94.5% of cases, while the oral suspension was used in 5.5% of cases. The majority of pharmacy visitors (89.0%) received rifaximin with a doctor's prescription, and 10.9% without a prescription, which emphasizes the importance of pharmaceutical care to prevent irrational use of the drug. The results of the study show that 92.7% of pharmacists provide recommendations on the safety of rifaximin use, and 78.2% recommend abstaining from alcohol during treatment. Only 21.8% of pharmacists warn about the possible staining of urine, which can cause concern for patients. The majority of pharmacists (89.1%) systematically ask women about possible pregnancy, which indicates their awareness of safe pharmacotherapy. Pharmacists also clarify the simultaneous use of rifaximin with other drugs: 32.7% ask about taking oral contraceptives, 7.3% – antiarrhythmic drugs, and 3.6% – warfarin. mailto:https://meshb.nlm.nih.gov/record/ui?ui=D002648Pharmacists can enhance the effectiveness of rifaximin treatment by preventing its uncontrolled use, emphasizing the importance of completing the treatment course and informing about possible adverse reactions. When providing pharmaceutical care to visitors taking rifaximin, pharmacists should educate them about potential changes in urine color. Additionally, pharmaceutical workers advise women taking oral contraceptives to use additional contraceptive methods while taking rifaximin.